Refugees in the Spanish press: A corpus-assisted study of the semantic prosody of the term refugiado from a diachronic perspective - Gema Alcaraz-Mármol; Jorge Soto-Almela (Sintagma, 2018)
This paper explores the semantic prosody of the lemma refugiado in the Spanish press over a 7-year period (2010-16) with the aim of examining the discursive representation of refugees in this textual genre. The study is concerned with diachronic and quantitative aspects, while focusing on the negative lexical units collocating with refugiado. The research is based on the analysis of a 1.8-million-word corpus of Spanish news articles about refugees that were extracted from the digital libraries of El País and El Mundo. The results show that the frequency of refugiado increases over the 2010-16 period, and so does its negative semantic prosody. This negativity –which is much higher in the last two years under study– is constructed through certain consistent collocates, seasonal collocates and patterns of language associated with refugees’ massive occupation and victimization.